Study on Effect of Surfactants on Dispersion Characteristics of Nanofluids - Saleh, Muhammad Ridhwan (IRC, 2016)
Nanofluids are the new engineering materials which comprise of nanometre size particles as an improver to modify the properties of common fluids to be suitable in various applications. The biggest issue in nanofluids is the settling of nanoparticles due to agglomeration among particles in the liquid. Previous studies are mostly using water-based nanofluids and water-based surfactants as the stabilizer but in this study, oil-based surfactants was used to examine its effects towards the dispersion characteristics of oil-based nanofluids. The dispersion behaviour of nanofluids using zinc oxide nanoparticles of 30 and 50 nm size; and magnesium oxide of 30 nm size in heat transfer fluid (thermal oil) has been observed. Standard batch sedimentation apparatus was used to determine the settling characteristics at various time periods with and without the addition of surfactants after been sonicated. Photographic method such as SEM was used to determine the shape of nanoparticles and agglomeration in nanoparticles. Other relevant methods such as FTIR and UV-vis spectroscopy was used to identify any reaction between nanofluids and surfactants and also the absorbency value of nanofluids. The results shows that surfactant TWEEN 60 is proven to enhance the nanofluid stability of MgO 30 nm in thermal oil